Marketing in Transition: Scarcity, Globalism, & Sustainability: Proceedings of the 2009 World Marketing Congress - Campbell, Colin L (Springer, 2015)
This volume includes the full proceedings from the 2009 World Marketing Congress held in Oslo, Norway with the theme Marketing in Transition: Scarcity, Globalism, & Sustainability. The focus of the conference and the enclosed papers is on marketing thought and practices throughout the world. This volume resents papers on various topics including marketing management, marketing strategy and consumer behavior.